Development of neonatal death clinical audit instrument - Setya Wandita; Fachmi PS Sinurat; Pancho Kaslam; Dian Anggraini; Wahyu Adiwinanto; Suci Harini; Jumhari Baco; Muslikhah Y Farhati (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2022)
Introduction: A neonatal death clinical audit is needed to improve the quality of care and prevent similar preventable neonatal deaths. This study aims to develop a neonatal death clinical audit instrument. Method: We developed a neonatal clinical death audit instrument for all death cases admitted to the nursery. The audit was started from the place of delivery for the inborn and arrival at the emergency room for the outborn. The instrument contains all aspect all aspects of case management. The audit was carried out by comparing the patient's management practices with the standard operating procedures. The last part of the instrument was the death information, assessment of deviations, and determination of avoidability. The instrument was tested twice, and pediatricians and neonatologists conducted an audit at several types of hospitals in Indonesia. The instrument was tested to audit 20 cases at six hospitals in 4 Provinces, and the second test was 37 cases at six hospitals in East Nusa Tenggara. The auditors of the first test were neonatologists and general pediatricians, while for the second test were general pediatricians. The average time of audit was 30 minutes. Results: The instrument could detect the deviations, cause of death, and avoidably. Conclusions: The instrument could identify deviations and determine avoidably neonatal death. Recommendations based on the deviations may improve the quality of care and prevent similar neonatal death.